Analisis Pengukuran Tingkat Produktivitas Produksi Dandang Aluminium Menggunakan Metode American Produktivity Center (APC) Pada CV. Cipta Jaya - Khairuddin, Khairuddin; Sutrisno, Sutrisno; Silviana, Nukhe Andri (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2024)
CV. Cipta Jaya is a company in the manufacture and assembly of aluminum casseroles located at Tembung Main Street No. 11 in Medan was founded by Mr. Daiman on May 23, 1998, with its dominant production of aluminum casseroles. The condition of employees at work was lacking enthusiasm and not focusing on the production process. The very modest use of machines and tools led to the nonoptimal production process. In addition, product sales on CV Cipta Jaya had decreased due to a lack of promotion in the mass media. This caused productivity in CV. Cipta Jaya was less effective and efficient so it needed to improve the production line. The purposes of this study were to determine the effective strategy for increasing productivity based on the company's conditions and the level of company profitability. The method used was The American Productivity Center (APC model). The results showed that the productivity level of CV. Cipta Jaya during the measurement period decreased. It was seen from all inputs as a whole in period 1 of -39.176 and period 3 of -39.176. The level of inconstant profitability fluctuates based on the above calculation; a decrease in productivity was followed by a decrease in profitability. It was proven in period 1 which fell by -17.1% and period 2 by 59.5%. Then, it increased in period 1 of energy input by 0.920 and capital by -1.205. The price improvement index increases every year, namely, period 1 by 1.0% and period 2 by 1.03%.